Relation between students’ expectations about their grade and metacognitive monitoring and a deeper understanding of metacognitive judgments (2021)
Metacognition is an important higher-order thinking process for successful learning. The present study investigated the relation between students’ (N = 65) expectations about their grade (expressed as difference scores between expected grade and actual grade) and their metacognitive monitoring accuracy and bias and the extent to which these difference scores in expected grade versus actual grade predicted accuracy and bias, employing an explanatory sequential quantitativeQUALITATIVE mixed method research design. The study also explored how students develop and refine metacognitive judgments and the types of strategies they employ during this process. Results revealed that there were significant relations between difference scores in expected grade versus actual grade and accuracy and bias (r = .02 to r = .89 in absolute value), and that difference scores significantly predicted both accuracy (R2 = .52) and bias (R2 = .69). Further, qualitative findings revealed that there were differences in how students developed and refined metacognitive judgments as a function of four aspects of learning: effort/preparation, strategy selection/implementation, planning, and evaluation. Educators should explicitly teach metacognitive monitoring skills to improve students’ selfregulated learning. Key words. Metacognition; Absolute accuracy; Absolute bias; Mixed method (Source: PsycINFO Thesaurus).